Evaluation of pH and total soluble solid (ºbrix) on the cariogenic and erosive potential of milk powder infantile formula (Research, Society and Development, 2022)
The objective of this study is to analyze the influence of pH and the amount of Total Soluble Solids on the ºBrix scale on the cariogenic and erosive potential of powdered infant formula. This is a laboratory study with 5 brands of powdered infant formula for children aged 6 to 36 months. Brands with intact packaging, stored in cool places and within the expiry date for consumption were included. Obtaining the Brixº was performed by refractometer and pH with a pHmeter with a cycle of three repetitions. Of the five brands tested, the sugar levels on the ºBrix scale were between 10.67 and 12.0, with all maras having total carbohydrate values ​​between 9.0 and 14.0 g, which are considered healthy. Regarding the pH, four had a pH lower than 7, being considered acidic and all above the critical pH (5.5) for dissolution of dental structures. It was concluded that by measuring pH and sugars on the Brixº scale, the brands analyzed were within acceptable standards for maintaining oral health, making these two factors positive determinants so as not to influence the cariogenic and/or erosive potential of milk powder infant formula.